Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1890/05-1991
|View full text |Cite
|
Sign up to set email alerts
|

WHAT MAKES GREAT BASIN SAGEBRUSH ECOSYSTEMS INVASIBLE BYBROMUS TECTORUM?

Abstract: Ecosystem susceptibility to invasion by nonnative species is poorly understood, but evidence is increasing that spatial and temporal variability in resources has large‐scale effects. We conducted a study in Artemisia tridentata ecosystems at two Great Basin locations examining differences in resource availability and invasibility of Bromus tectorum over elevation gradients and in response to direct and interacting effects of removal of perennial herbaceous vegetation and fire. We monitored environmental condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
587
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 534 publications
(627 citation statements)
references
References 103 publications
31
587
3
1
Order By: Relevance
“…Artemisia t. ssp. vaseyana steppe recovery following fire in piñon-juniper woodlands often varies in composition and rate, as a consequence of differing fire extent and severities, seed source, abundances and competitive abilities of native and exotic species, ecological site characteristics, herbivory and environmental variation (Barney and Frischknecht 1974;Koniak 1985;Chambers et al 2007;Rau et al 2008;Ziegenhagen and Miller 2009;Bates et al 2011 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Artemisia t. ssp. vaseyana steppe recovery following fire in piñon-juniper woodlands often varies in composition and rate, as a consequence of differing fire extent and severities, seed source, abundances and competitive abilities of native and exotic species, ecological site characteristics, herbivory and environmental variation (Barney and Frischknecht 1974;Koniak 1985;Chambers et al 2007;Rau et al 2008;Ziegenhagen and Miller 2009;Bates et al 2011 …”
Section: Discussionmentioning
confidence: 99%
“…This level of perennial grasses was adequate for density to recover 4 years after fire and, in combination with higher densities of perennial forbs than that on Phase 3 sites, likely limited B. tectorum increases on Phase 2 sites. Others have indicated that greater presence and recovery of perennial herbaceous vegetation prevents annual grasses from dominating after fire in sagebrush steppe (Chambers et al 2007;Davies et al 2008;Bates and Svejcar 2009;Bates et al 2011;Condon et al 2011). Another element that may have supported native plant recovery on the Phase 2 sites was, potentially, a more complete soil seed bank.…”
Section: Herbaceous and Ground Cover Responsementioning
confidence: 99%
See 1 more Smart Citation
“…These declines have cascading ecological effects, characterized by positive feedback loops between community invaders and fire, with irreversible changes in ecosystem structure and function (D'Antonio and Vitousek 1992, Brooks et al 2004, Balch et al 2013. The abundances of these steppe foundation species correlate strongly with resilience to fire and resistance to invasion (Chambers et al 2007, Brooks and Chambers 2011, Condon et al 2011, Davies et al 2012, Reisner et al 2013. The uptake of soil nitrogen and water by big sagebrush and by bunchgrasses has been shown through removal experiments to reduce community invasibility (Chambers et al 2007, James et al 2008, Mata-Gonzalez et al 2008, Prevey et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The abundances of these steppe foundation species correlate strongly with resilience to fire and resistance to invasion (Chambers et al 2007, Brooks and Chambers 2011, Condon et al 2011, Davies et al 2012, Reisner et al 2013. The uptake of soil nitrogen and water by big sagebrush and by bunchgrasses has been shown through removal experiments to reduce community invasibility (Chambers et al 2007, James et al 2008, Mata-Gonzalez et al 2008, Prevey et al 2010. Additionally, the severity of infestations of cheatgrass and another invasive annual grass, medusahead (Taeniatherum caput-medusae), are inversely correlated with the abundances of pre-existing native perennial bunchgrasses (Davies 2008, Condon et al 2011, Davies et al 2012, Reisner et al 2013.…”
Section: Introductionmentioning
confidence: 99%